Investigations into the intramolecular geminal acylation reaction - Blanchard, Angela N., 1976- (2000)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2000. Chemistry Bibliography: leaves 81-83 The geminal acylation reaction, initially introduced by Kuwajima and co-workers, has been developed into a synthetically useful method of creating cyclic diketones by reacting l,2-bis[(trimethylsilyl)oxy]cyclobutene (1) with aldehydes, ketones, or acetals. To date, all examples of the reaction are intermolecular. The focus of this research was to develop methodology for an intramolecular geminal acylation. This process would lead to bridged compounds with two carbonyl functionalities. -- Compounds that should be capable of performing an intramolecular germinal acylation have been synthesized. These compounds possess a reactive functionality similar to that of 1, and an acetal moiety. Attempts at performing this reaction have been made and the results are quite promising. Several bridged diketones have been generated. There have been other compounds isolated that indicate that this reaction does proceed, however isolating the desired products has been problematic due to destruction of the bridged diketones within the reaction mixture.